EFEKTIVITAS PEMBELAJARAN BERBASIS PROYEK TERHADAP KREATIVITAS BELAJAR MATEMATIKA SISWA SD - Saskia Setiawati; Feny Rita Fiantika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low creativity in mathematics learning among elementary school students. This is indicated by students’ lack of ability to solve problems in various ways, limited ability to develop new ideas, and low participation during mathematics learning activities. One effort to improve students' creativity is by implementing Project Based Learning This study aims to determine the effectiveness of project-based learning on elementary school students’ creativity in mathematics learning. This research used a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The subjects of this study were fourth grade students of SDN Tenggilis Mejoyo Surabaya. Data collection techniques included tests, observations, and documentation. The results showed that project-based learning was effective in improving students’ creativity in mathematics learning. Students in the experimental class showed better improvement in creativity compared to students in the control class. This can be seen from the indicators of creativity including fluency, flexibility, originality, and elaboration which increased after the implementation of project-based learning.